Managerial competence of future specialists of the education system (Preschool education and upbringing) and medicine in the comparative aspect - Abilbakieva, Galiya; Knissarina, Malika; Adanov, Kuanyshbek; Seitenova, Salima; Bekeshova, Gulmira (Opción, 2018)
It is proposed the solution of one of the urgent tasks in pedagogical science and practice – development of managerial competence at future specialists in the sphere of medicine and education (preschool education and upbringing). The purpose of our research consists in comparison of the obtained data on diagnostics of managerial competence at future specialists in the aspect of two empirical researches, conducted in the different cities of Kazakhstan - Almaty and Aktobe. On the basis of the obtained data it is planned to develop psychology and pedagogical conditions for formation and development of managerial competence at future specialists of the preschool organizations and medical practice in the conditions of vocational training in higher education institution.Keywords: managerial skills, managerial competence, future specialist of medical practice, information and communication technologies, education management.